A conceptual root zone model to calculate the application amount and frequency of water available for recharge - Flores-López, Francisco; Arrate, David; Bastani, Mehrdad (Frontiers in Water, 2025)
Periods of extreme dry weather and extreme wet weather have stressed water resources worldwide. California’s water management sectors face an increased risk from climate change, and consequently the California Department of Water Resources has investigated the benefits of using floodwater for managed aquifer recharge (Flood-MAR). Flood-MAR requires the implementation of an integrated surface-ground water resources approach that can address watershed hydrologic processes from the atmosphere to the valley floor and the aquifer systems. In this process, it was learned that there is a need to develop a root-zone model with the capability of determining both the amount and the frequency of the applied water at field scale using crop and soil data to avoid damaging agricultural crops. Therefore, the following factors were considered: soil suitability, crop suitability, and soil oxygen depletion due to the application of water available for recharge. IDC (Integrated Demand Calculator) is a stand-alone root zone component of the Integrated Water Flow Model (IWFM) which provides conceptual features for simulating root zone saturation levels. We propose a simple conceptual root-zone model to calculate the application amount and frequency of water available for recharge through the implementation of Flood-MAR operations on agricultural fields. The method is based on soil-land use combination, and crop saturation tolerance considering seasonal patterns during a long-term application of water available for recharge. The results of the conceptual root-zone model were (i) the amount of applied water, (ii) the reached saturation water content in the root zone not exceeding 75 percent saturation to avoid inhibiting plant respiration and growth, (iii) the potential return interval between applications for each soil-land use combination, and (iv) the amount of applied water needed to maintain six inches of ponding water depth in fallow land. The model proved it’s a useful tool for water management in practice where its utility is outstanding, and it provides valuable information to guide planners, water district managers and farmers when implementing Flood-MAR.